2023
DOI: 10.1371/journal.pone.0287768
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of MUC4 are associated with susceptibility to and mortality of colorectal cancer and exhibit synergistic effects with LDL-C levels

Min Jung Kwon,
Jeong Yong Lee,
Eo Jin Kim
et al.

Abstract: As a disease with high mortality and prevalence rates worldwide, colorectal cancer (CRC) has been thoroughly investigated. Mucins are involved in the induction of CRC and the regulation of intestinal homeostasis but a member of the mucin gene family MUC4 has a controversial role in CRC. MUC4 has been associated with either decreased susceptibility to or a worse prognosis of CRC. In our study, the multifunctional aspects of MUC4 were elucidated by genetic polymorphism analysis in a case-control study of 420 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(46 reference statements)
0
1
0
Order By: Relevance
“… 37 MUC4 genetic variants were associated with mortality and susceptibility to CRC. 38 These findings showed that MUC4 mutations were closely related to CRC metastasis and prognosis and could be novel biomarkers for the prediction of CRC patients’ prognosis.…”
Section: Discussionmentioning
confidence: 80%
“… 37 MUC4 genetic variants were associated with mortality and susceptibility to CRC. 38 These findings showed that MUC4 mutations were closely related to CRC metastasis and prognosis and could be novel biomarkers for the prediction of CRC patients’ prognosis.…”
Section: Discussionmentioning
confidence: 80%